2005
DOI: 10.1001/archopht.123.4.497
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Delay of Surgical Intervention in Adult Strabismus

Abstract: Background: It has been our impression that adult patients with strabismus frequently delay surgical intervention. Objectives: To determine the length of time adult patients waited before undergoing strabismus surgery and to determine the reasons why these delays occurred. Design, Setting, and Participants: Prospective survey of consecutive patients who delayed strabismus surgery for more than 1 year. Intervention: Preoperative survey. Main Outcome Measures: The primary outcome measure was time between the ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 13 publications
0
35
0
1
Order By: Relevance
“…1 Its most noticeable effect is on the facial appearance of affected individuals; however, the widespread belief that corrective squint surgery is a purely cosmetic procedure is incorrect. First, it seeks to restore the normality disrupted by a disease process rather than gild or glamorise.…”
Section: Introductionmentioning
confidence: 99%
“…1 Its most noticeable effect is on the facial appearance of affected individuals; however, the widespread belief that corrective squint surgery is a purely cosmetic procedure is incorrect. First, it seeks to restore the normality disrupted by a disease process rather than gild or glamorise.…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity analysis revealed that the cost per QALY was substantially increased when the duration of alignment was limited to 10 years. On the other hand, Coats and associates [13] reported that adults with strabismus tend to postpone surgical intervention by 19.9 years on average. If the effect of surgical alignment were maintained for a long time, strabismus surgery performed at a younger age would be more cost-effective, given the relatively long life expectancy.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these favorable outcomes, the value of adult strabismus surgery appears to be underestimated and is sometimes regarded as only a cosmetic treatment, even by ophthalmologists [13]. Unlike other eye surgeries, such as cataract surgery and retinal detachment surgery, adult strabismus surgery does not usually improve the visual acuity nor save the eyes from permanent visual loss.…”
Section: Introductionmentioning
confidence: 99%
“…Strabismus, which is present in approximately 4% of the population (Coats et al, 2005), represents a complex problem of eye alignment, binocularity and cosmetics. If strabismus occurs before visual maturity, abnormal binocular interaction that altersthe binocular depth perception resulting in amblyopia, suppression and anomalous retinal correspondence develops.…”
Section: Introductionmentioning
confidence: 99%